Тенденции обучения проектированию электронных устройств на микроконтроллерах - Зубков, О. В. (ХНУРЕ, 2019)
The world experience in the development of embedded systems on microcontrollers is analyzed. The main leaders in the production of microcontrollers and the growth dynamics of sales of their products are identified. Revealed trends in the number of projects with embedded real-time operating systems and processors with ARM architecture. The requirements for the training of specialists in the field of microcontroller programming are formulated.
Keywords: мікроконтролер; вища освіта; STM32; ARM